2019
DOI: 10.11646/zootaxa.4590.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Revision of black fungus gnat species (Diptera, Sciaridae) described from the Hawaiian Islands by D.E. Hardy and W.A. Steffan, and a contribution to the knowledge of the sciarid fauna of the Galápagos Islands

Abstract: On the Hawaiian Islands 22 sciarid species were detected, belonging to the following ten genera: Austrosciara Schmitz & Mjöberg, Bradysia Winnertz, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Hyperlasion Schmitz, Lycoriella Frey, Phytosciara Frey, Pseudolycoriella Menzel & Mohrig and Scatopsciara Edwards. The revision resulted in new combinations for the following five species: Austrosciara hawaiiensis (Hardy) comb. n., Corynoptera prominens (Hardy) comb. n., Cratyna adrostylata (Hardy) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Considering the feeding habits of B. hygida , we suggest that its classification in the Pseudolycoriella group is probably correct. Bradysia is a species rich genus that has been acknowledged as one of the most morphologically controversial groups within the Sciaridae family (Mohrig et al, 2013; Mohrig et al, 2019). Recent studies have shown that DNA barcoding is a useful tool to identify both immature forms and adults of the Bradysia genus (Arimoto et al, 2018; Shin et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the feeding habits of B. hygida , we suggest that its classification in the Pseudolycoriella group is probably correct. Bradysia is a species rich genus that has been acknowledged as one of the most morphologically controversial groups within the Sciaridae family (Mohrig et al, 2013; Mohrig et al, 2019). Recent studies have shown that DNA barcoding is a useful tool to identify both immature forms and adults of the Bradysia genus (Arimoto et al, 2018; Shin et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Diagnoses of the species are generally based on the keys and descriptions in Hippa et al (2010), Menzel and Mohrig (2000), and Mohrig et al (2013). The distribution data of the species discussed were compiled from the following publications: Arimoto et al (2018), Babytskiy et al (2019), Broadley et al (2018), Ebejer and Gatt (2021), El Ouazzani et al (2019), Heidari Latibari et al (2016a, Heller and Menzel (2017), Hippa et al (2010), Katumanyane et al (2020), Menzel & Elsayed (2013), Menzel and Satayeva (2010), Menzel and Smith (2009), Menzel and Vilkamaa (2021), Menzel et al (2003Menzel et al ( , 2020aMenzel et al ( , 2020b, Mohrig et al (2001Mohrig et al ( , 2013Mohrig et al ( , 2019, Shin et al (2015), Sohier et al (2012), Steffan (1969Steffan ( , 1974, Sueyoshi and Yoshimatsu (2019), Ye et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The identification of species was carried out according to the keys, descriptions, and figures by several authors [1,[3][4][5]7,25,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. The morphological terminology follows [7,70,81], with some minor adaptations to abbreviations (see Section 2.5, 'Morphological abbreviations').…”
Section: Species Identification and Classificationmentioning
confidence: 99%